ANALISIS EFISIENSI EFEKTIFITAS DAN KEMANDIRIAN KEUANGAN PADA BADAN LAYANAN UMUM DI UNIVERSITAS TADULAKO - Fajriani, Fajriani (Katalogis, 2018)
The study intends to determine and analyse: 1) financial efficiency of Public Service Agency in Tadulako University; 2) financial effectiveness of Public Service Agency in Tadulako University; 3) financial independency of Public Service Agency in Tadulako University. Type of study is descriptive, which is aimed to comprehensively analyse and describe financial efficiency, effectiveness, and independency of the Public Service Agency in Tadulako University. The study finds that the efficiency ratio indicates that financial management of Tadulako University is less efficient with an average ratio of 105%. Financial management effectiveness ratio of 104% or very effective in average. This is indicate by greater revenue than planned realizations. Financial independence management ratio of Tadulako University in six years is 34% or in the consultative category.